Program Bimbingan Belajar Guna Meningkatkan Prestasi Akademik di Desa Sekutur Jaya - Krisma Oktaviani; Venty Meilasari (Pengabdian Kepada Masyarakat Cendekia, 2024)
Abstract: Education is one of the main pillars in a country's development. However, the reality is that not all levels of society have equal access to quality education, for example in rural areas. Limited infrastructure is one of the factors that influences the academic achievement of students in rural areas. In an effort to overcome this, tutoring programs emerged as an alternative. This program is implemented by providing study guidance to students in the Allied Jaya village environment. With this program, students experience increased learning achievement, are more motivated and confident in facing the subject matter.